(untitled) (Agromet, 2020)
This study aims to modify the idea of WK99-analyzing the existence of signature in wavenumber and frequency spectrum when the analyzed Outgoing Longwave Radiation (OLR) data is associated with a unique phenomenon in Maritime Continent (MC), Borneo vortex (BV). Although BV is often related to easterly equatorial wave disturbances, there was no specific study to examine its behavior in the spectral domain. The purpose of this study is to develop a method to diagnose certain signatures of BV through spectrum analysis of OLR data when BV occurs. In contrast to previous studies, to present the unique phenomenon in MC as a target for diagnostics, spectrum analysis was performed by Spherical Harmonics (SH). This method used trigonometric and associated Legendre functions which present zonal and meridional structure, respectively. Hence, the separation of antisymmetric and symmetric patterns to the equator in this method was considered better than WK99. The results showed that the spectral signatures of BV were characterized by enhancements of westward propagating mixed Rossby gravity (MRG) with zonal wavenumbers of 5-10 and frequencies of 0.12-0.2 cycle per day (cpd) (periods of 5-8 days). Moreover, the spectrum of the wave is getting stronger for longer BV duration.